Pengaruh Pendidikan Kesehatan Dengan Metode Simulasi Pertolongan Pertama (Log Roll) Pada Korban Dengan Indikasi Cedera Tulang Belakang Di Pendidikan Informal Kecamatan Tempuran Magelang - Akhmad Rifai; Moh Ilyas (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: Prevalence in Indonesian society in 2007 was 7.5%, with several factors causing traffic and crossing sharp/ blunt objects. In 2013 there was an increase in the prevalence of trauma to 8.2%, with the highest order of injuries being down 40.9%, motorcycle accidents (40.6%), trauma due to sharp/blunt objects 7.3%, other land transportation 7, 1% and 2.5% fallout. To equip ordinary students in carrying out the Log roll Skills to help victims with spinal trauma need to do log roll Skills training. In this regard, researchers intend to conduct research on "The Effect of Health Education with First Aid (Log Roll) Simulation Methods on Spinal Injuries in Tempuran Informal Education in Magelang". Methods: This research is experimental research with the PreTest-Post Test Group design approach. through hypothesis testing research. The population of this research was 50 people in the cloud (Ponpes Roudlotuttulab students). Statistical test on paired groups using the nonparametric Wilcoxon test. Result: Based on the Wilcoxon test results, it can be concluded that 50 respondents who log roll training can be drawn in the conclusion that the majority of students have a basic score of 0.001 which means there is a difference that takes place between before and after training. Conclusion: The suggestion put forward in this study is that education and log roll action training for lay people, especially students, continues to be held at other Islamic boarding schools to improve the skills of log roll action skills suspected in victims with spinal injuries.